Effect of acute exposure of Hg on physiological parameters and transcriptome expression in silkworms (Bombyx mori) - Wen, Huanhuan; Wang, Yanan; Ji, Yongqiang; Chen, Jing; Xiao, Yao; Lu, Qixiang; Jiang, Caiying; Sheng, Qing; Nie, Zuoming; You, Zhengying (Frontiers in Veterinary Science, 2024)
Mercury (Hg) contamination poses a global threat to the environment, given its elevated ecotoxicity. Herein, we employed the lepidopteran model insect, silkworm (Bombyx mori), to systematically investigate the toxic effects of Hg-stress across its growth and development, histomorphology, antioxidant enzyme activities, and transcriptome responses. High doses of Hg exposure induced evident poisoning symptoms, markedly impeding the growth of silkworm larvae and escalating mortality in a dose-dependent manner. Under Hg exposure, the histomorphology of both the midgut and fat body exhibited impairments. Carboxylesterase (CarE) activity was increased in both midgut and fat body tissues responding to Hg treatment. Conversely, glutathione S-transferase (GST) levels increased in the fat body but decreased in the midgut. The transcriptomic analysis revealed that the response induced by Hg stress involved multiple metabolism processes. Significantly differently expressed genes (DEGs) exhibited strong associations with oxidative phosphorylation, nutrient metabolisms, insect hormone biosynthesis, lysosome, ribosome biogenesis in eukaryotes, and ribosome pathways in the midgut or the fat body. The findings implied that exposure to Hg might induce the oxidative stress response, attempting to compensate for impaired metabolism. Concurrently, disruptions in nutrient metabolism and insect hormone activity might hinder growth and development, leading to immune dysfunction in silkworms. These insights significantly advance our theoretical understanding of the potential mechanisms underlying Hg toxicity in invertebrate organisms.